P4.119 How Can we improve partner notification following hiv diagnosis? – a qualitative study of men who have sex with men in melbourne. (8th July 2017) - Tomnay, Jane; Hulme-Chambers, Alana; Bilardi, Jade; Fairley, Christopher; Huffam, Sarah; Chen, Marcus
Abstract : Introduction: Improved partner notification (PN) following HIV diagnosis could help control HIV among men who have sex with men (MSM). However, there is little evidence exploring what this experience is like for Australian MSM and how achievable it is in the era of the internet and smartphones. Methods: MSM recently diagnosed with HIV were recruited from three health services in Melbourne for a semi-structured interview about PN experiences. Interviews were transcribed verbatim for thematic analysis using a combined deductive/inductive approach whereby themes were derived from both previous literature, the research questions and interview schedule and inductively from emergent and recurrent themes arising from the data. Results: Three main themes arose: the fear of PN and HIV disclosure; partners' unexpected reactions; and the need for more support for PN. MSM found partner notification difficult and uncomfortable and described fear about potential repercussions of PN. However, they felt it was the right thing to do and all partners should be notified where ever possible. Regular partners were more likely to be notified, and in person, due to the availability of contact information but more notably due to a sense of moral responsibility. Men commonly had few contact details for casual partners and preferred partner notification strategies that allowed them to remain anonymous, largely reflecting the reasons for and ways in which they met casual partners: online or through apps and predominantly for once-off, anonymous sex. Most described unexpected positive responses from partners who were contacted personally by the men. Our study also showed that these participants required professional support to carry out PN, especially with casual partners, as well as support around understanding the implications of and treatments relating to being HIV positive. Conclusion: PN could be improved by offering more options that allow the index patient to remain anonymous, particularly when notifying casual partners.